1999
DOI: 10.1088/0953-8984/11/32/316
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer studies of the alloys Fe3Ga4, (Fe1-xTix)3Ga4and (Fe1-yCry)3Ga4

Abstract: The crystal structure of the alloy Fe3Ga has four inequivalent crystallographic iron sites. Mössbauer spectra recorded at 4.2 K were able to be fitted with four sextets corresponding to these sites. Measurement of the hyperfine fields Bhf gave values 271 kG, 191 kG, 152 kG and 195 kG respectively. For the series (Fe1-xTix)3Ga4 spectra were recorded at 4.2 and 300 K for x = 0.05, x = 0.10 and x = 0.15. These spectra were fitted to five sextets, each associated with a distinct iron site. The magnetic ordering te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The isomer shifts observed herein are between 0.50 and 0.53 mm/s at 4.2 K and are ca. 0.40 mm/s at 295 K. In the Ln 2 Fe 17 , LnFe 11 Ti, and LnCo 4− x Fe x B , compounds, the isomer shifts are in the range of zero to 0.2 mm/s at 4.2 K. In contrast, for both iron in a gallium host and iron in Fe 3 Ga 4 , the isomer shifts are significantly more positive, that is, 0.50 and 0.31 mm/s at 4.2 and 295 K, respectively. In all of the gallium-containing compounds, the iron atoms have gallium near neighbors and share their 3d electrons with these gallium near neighbors.…”
Section: Resultsmentioning
confidence: 94%
“…The isomer shifts observed herein are between 0.50 and 0.53 mm/s at 4.2 K and are ca. 0.40 mm/s at 295 K. In the Ln 2 Fe 17 , LnFe 11 Ti, and LnCo 4− x Fe x B , compounds, the isomer shifts are in the range of zero to 0.2 mm/s at 4.2 K. In contrast, for both iron in a gallium host and iron in Fe 3 Ga 4 , the isomer shifts are significantly more positive, that is, 0.50 and 0.31 mm/s at 4.2 and 295 K, respectively. In all of the gallium-containing compounds, the iron atoms have gallium near neighbors and share their 3d electrons with these gallium near neighbors.…”
Section: Resultsmentioning
confidence: 94%
“…Thus, there is a significant magnetic entropy associated with the AFM state above that of the FM state tending to favor ferromagnetism at low T . In contrast, the Fe 3 Ga 4 crystal structure is not obviously layered and frustration is highly unlikely [28] so that a similar mechanism is unlikely to play a role. In EuRh 2 Si 2 the low-T phase is thought to be a spin spiral which transitions to fan-like structure for fields along the easy plane [49].…”
Section: Discussion and Summarymentioning
confidence: 99%
“…The reduction of H mm with cooling indicates a continuous decrease in the energy difference between the FM and AFM states until a first-order transition at T 1 where the FM state emerges as the ground state. Above 400 K χ is reduced [24] and the Mössbauer spectra evolves into a single broad line [28] so that a critical temperature for magnetic ordering was identified at 392 K. Mössbauer experiments have also established a different magnetic moment for each of the four unique crystallographic Fe-sites [24,28] increasing the complexity of this binary system. Duijn et al [26,27] explored the specific heat and thermal expansion of Fe 3 Ga 4 finding only a small anomaly in the thermal expansion at T 1 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that doping can effectively tune the IDSW to FM transition temperature as well as the low temperature FM to ISDW transition. 16,[28][29][30][31] Similarly, previous work has shown that external pressure is effective at tun- ing the low temperature FM-ISDW transition temperature, but the effect on the high temperature ISDW-FM transition temperature has not been reported. 20,32 From these works, it appears that intermediate IDSW is sensitive to effects caused by doping through electron count changes and/or structural changes which in turn effect the electronic structure in this regime; although this has not be rigorously studied.…”
Section: Introductionmentioning
confidence: 96%